Radio frequency identification (RFID) : evaluation of the technology supporting the development of Program Latihan Khidmat Negara (PLKN) participants tracking application - Ismail, Ishak; Yii, George Chii Cheng; Nik Mohd. Nizam, Nik Mohd. Habibullah (Institute of Electrical and Electronics Engineering (IEEE), 2007)
Radio Frequency Identification technology has been adopted into goods tracking, human tracking and identification of valuable items to fulfill the needs of identification. Reliable RFID communication requires good communication protocols as well as decision support protocols. The purpose of this paper is to review the current RFID technology and to explain the anti-collision protocol which is the communication protocol that eliminates the collisions between reader and tag as it will prevent reader from obtaining data from tags. Besides, this paper will also introduce the positioning protocol as a part of decision support protocol which is used to help the system to determine the location of required tag. These protocols are the random back-off anti-collision protocol which uses counter to generate random duration for next transmission to avoid tags from transmitting at the same time, simple positioning protocol and receiving power based triangulation method using Heronpsilas formula for positioning protocol use the concept multi readers to formulate the location of tag. Simulations have been done to illustrate how the protocols work. These protocols may be used in certain low end systems which cater fewer functions and limited number of mobility tags. As a conclusion, these protocols are able to be implemented into National Service participants tracking application to fulfill the requirements of tracking moving objects.